Socio-economic profile and challenges of fishing communities:A Case study of Chhirpani Reservoir in Kabirdham district, Chhattisgarh - Beishamayum, Nightingale Devi; K, Kiran; Kaiwart, Lavanya; Bhaskar, Rakesh; Dhruw, Vidya (Journal of Indian Fisheries Association, 2023)
Fisheries plays a vital role in offering sustenance, job opportunities, and entrepreneurial avenues to over 2.8crore individuals engaged in fishing and aquaculture at the grassroots level with thousands of people across theentire value chain (Department of Fisheries, 2023). India holds the distinction of being the global leader ininland capture fish production (SOFIA, 2022). Notably, the inland fisheries and aquaculture have surged twofold, rising from 61.36 lakh tons in 2013-14 to 121.12 lakh tons by 2021-22. The present study aims to providean assessment of the socio-economic status and challenges of the fisher community in Chhirpani Reservoir,located in Kabirdham, Chhattisgarh. The primary data for socio-economic assessment and challenges werecollected through qualitative research using semi-structured questionnaires and in-depth interviews withfishermen. The findings highlighted the dominant age group of fishers falling within 40-59 years, with malerepresentation of 75%. Moreover, it was observed that 57% of fishers reside in Pucca houses constructedunder the "Pradhan Mantri Awaas Yojna" scheme. The absence of a primary healthcare center in their villagesnecessitates an arduous 7-kilometer journey to access healthcare services, resulting in increased expenditure.Additionally, the study revealed that 52% of fishers have received only primary education and 35% were foundto be illiterate. Subsequently, challenges they faced were discussed emphasizing the need for improvedinfrastructure, including health centers and schools in fishing villages, to uplift fishers' welfare and theirstandard of living. By addressing these challenges, the policymakers and stakeholders can contribute to thesustainable development and well-being of the fisher community in Chhirpani reservoir.